Anti-Inflammatory Activity of the Fruit Extract of Benincasa hispida - Kadam, Deepak; Lele, Smita (Journal of Nutritional Therapeutics, 2014)
Benincasa hispida (Ash gourd, family: Cucurbitaceae) is well known for its medicinal property. In the Ayurvedic system, it is used as a rejuvenating agent and in the treatment of nervous disorders. Methanolic and petroleum fruit extracts was subjected to evaluation of phytochemicals and acute oral toxicity study. Further, Anti-inflammatory activity was performed using human red blood cell (HRBC) membrane stabilization assay and carrageenan induced paw edema in rat. Oral administration of methanolic extract of concentration (350 mg/kg) significantly reduced the paw edema (P < 0.05) in a dose dependent manner as compared to carrageenan induced rats.